The Chaperone Protein GRP78 Promotes Survival and Migration of Head and Neck Cancer After Direct Radiation Exposure and Extracellular Vesicle-Transfer - Schneider, Michael; Winkler, Klaudia; Kell, Rosemarie; Pfaffl, Michael W.; Atkinson, Michael J.; Moertl, Simone (Frontiers in Oncology, 2022)
Background and purpose: Increased levels of the chaperone protein Grp78 have been implicated in poorer outcomes of cancer therapy. We have therefore explored the functional connection between the expression of Grp78 and the development of radioresistance and metastatic behavior in HNSCC. Material and methods: The association between gene expression of Grp78 and survival in HNSCC patients was examined using the TCGA database. The influence of ionizing radiation on the Grp78 levels in HNSCC cell lines, their secreted extracellular vesicles (EV) and non-irradiated EV-recipient cells was investigated by Western Blot and FACS. The consequences of chemical inhibition or experimental overexpression of Grp78 on radioresistance and migration of HNSCC cells were analyzed by clonogenic survival and gap closure assays. Results: Elevated levels of Grp78 RNA in HNSCC correlated with poorer overall survival. Radiation increased Grp78 protein expression on the surface of HNSCC cell lines. Experimental overexpression of Grp78 increased both radioresistance and migratory potential. Chemical inhibition of Grp78 impaired cell migration. EVs were identified as a potential source of increased Grp78 content as elevated levels of surface Grp78 were found in EVs released by irradiated cells. These vesicles transferred Grp78 to non-irradiated recipient cells during co-cultivation. Conclusions: We have identified the chaperone protein Grp78 as a potential driver of increased radioresistance and motility in HNSCC. The uptake of Grp78-rich EVs originating from irradiated cells may contribute to a poorer prognosis through bystander effects mediated by the transfer of Grp78 to non-irradiated cells. Therefore, we consider the chaperone protein Grp78 to be an attractive target for improving radiotherapy strategies.